Berberine in cardiovascular therapy: bridging modern pharmacology with the traditional Chinese botanicals Huanglian (黄连), Huangbai (黄柏), Amur Cork Tree (黄檗), and Gong Lao Mu (亮叶十大功劳) - Seema Sharma; Sampat Singh Tanwar (Pharmacological Research - Modern Chinese Medicine)
Purpose: . This review aims to explore the current pharmacological evidence supporting the use of berberine, a bioactive alkaloid, in cardiovascular therapy, and to bridge this modern understanding with its traditional use in Chinese medicine through the botanicals Huanglian (黄连), Huangbai (黄柏), Amur Cork Tree (黄檗), and Gong Lao Mu (亮叶十大功劳). Method: We performed a comprehensive literature search across PubMed, CNKI, Web of Science, Scopus, ScienceDirect, and Google Scholar (inception to May 2025) to identify studies on berberine's (TCM) use in cardiovascular disorders. Our search used keywords like ''Berberine,'' ''Cardiovascular therapy,'' ''TCM,'' and specific botanical names (e.g., ''Huanglian''). We aimed to understand berberine's effectiveness and its molecular mechanisms in cardiovascular health. From 500 initial articles, we selected 250 relevant to our study on berberine's efficacy in various cardiovascular outcomes. Results: Modern pharmacological studies demonstrate that berberine exhibits significant cardiovascular benefits through multiple mechanisms of action. These include lipid-lowering effects by upregulating LDL receptors and inhibiting PCSK9, antihypertensive effects via vasodilation and modulation of the renin-angiotensin-aldosterone system, antiarrhythmic properties by affecting ion channels, and improvement in cardiac function in heart failure models. Traditionally, Huanglian, Huangbai, Amur Cork Tree, and Gong Lao Mu, all rich sources of berberine, have been used in Traditional Chinese Medicine (TCM) to treat symptoms aligning with cardiovascular disorders, such as palpitations, chest distress, and edema. The modern pharmacological findings largely corroborate these traditional applications, highlighting berberine as a key active component responsible for the observed therapeutic effects. Conclusion: Berberine holds significant promise as a therapeutic agent in cardiovascular disease, supported by both modern pharmacological investigations and its long history of use in TCM through berberine-rich botanicals like Huanglian, Huangbai, Amur Cork Tree, and Gong Lao Mu. Further well-designed clinical trials are warranted to fully elucidate the therapeutic potential and optimize the clinical application of berberine and these traditional herbs in the prevention and management of various cardiovascular conditions.